Comprehensive Characterization of Transforming Growth Factor Beta Receptor 1 in Stomach Adenocarcinoma Identifies a Prognostic Signature for Predicting Clinical Outcomes and Immune Infiltrates - He Y; Zhang H; Zhang Y; Wang P; Zhu K; Ba Y (International Journal of General Medicine, 2022)
Yi He,1,* Haiyang Zhang,1,* Yan Zhang,1,2,* Peiyun Wang,1 Kegan Zhu,1 Yi Ba1 1Tianjin Medical University Cancer Institute and Hospital, National Clinical Research Center for Cancer, Tianjin’s Clinical Research Center for Cancer, Key Laboratory of Cancer Prevention and Therapy, Tianjin, 300060, People’s Republic of China; 2Department of Gastroenterology, Tianjin Haihe Hospital, Tianjin, 300350, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yi Ba, Email bayi@tjmuch.comBackground: Stomach adenocarcinoma (STAD) ranks as the third leading cause of cancer death worldwide. TGF‑β receptor 1 (TGFBR1), serving important roles in the TGF‑β family, the mechanisms whereby TGFBR1 governs tumor progression, immune cell infiltration in STAD remains unintelligible.Methods: We used the TCGA, GEPIA, and HPA databases to explore TGFBR1 expression in STAD, the correlation between TGFBR1 expression and the clinical features. A receiver operating characteristic (ROC) curve and nomogram were constructed, and LASSO (the Least Absolute Shrinkage and Selection Operator)-selected features were used to build the TGFBR1 prognostic signature. GSEA is used to find the potential mechanism of TGFBR1 to promote the malignant process of STAD. We explored the influence of the TGFBR1 on the immune microenvironment of STAD through the TIMER2.0 and GEPIA database.Results: In our study, TGFBR1 expression was significantly elevated in STAD and positively co-expression with pathologic stage, lymph node metastases (LNM) stage and histopathological grade. Nine factors with non-zero coefficients were identified by LASSO-selected features. Survival analysis revealed that patients with high TGFBR1 had shorter OS, FP, and PPS. Multivariate Cox analysis revealed that TGFBR1 was an independent prognostic factor for OS in STAD. The ROC analysis suggested that high diagnostic value with the AUC of TGFBR1 was 0.739. GSEA revealed that high TGFBR1 expression was correlated with pathway in cancer, MAPK signaling pathway, NOTCH signaling pathway, and VEGF-C production. ssGSEA showed that TGFBR1 is correlated with NK cells, Tem and Th17 cells. Furthermore, elevated TGFBR1 expression was found to be significantly correlated with several immune checkpoint and immune markers associated with immune cell subsets.Conclusion: In summary, TGFBR1 could be a prognostic biomarker and an important regulator of immune cell infiltration in STAD. The present study revealed the probable underlying molecular mechanisms of TGFBR1 in STAD and provided a potential target for improving the prognosis.Keywords: TGFBR1, STAD, prognosis, immune infiltration, bioinformatics